PROSES MANUFAKTUR MESIN PENCACAH SAMPAH ORGANIK BERBAHAN BAKAR BIOMASSA - Astrid Fildzah Nabila Rozma (2021)
Indonesia is experiencing several problems including waste and increased energy use when energy availability is running low. Wood pellets are a source of biomass energy that can be utilized because of their low CO2 emissions and low price. The process of designing this tool is expected to produce tools that can help waste management with biomass energy sources so that it can be seen what manufacturing processes are carried out and the production costs incurred. Wood pellets are used as fuel to generate electricity which is converted by a Thermo Electric Generator (TEG). After being converted by TEG, electricity will drive the dynamo which is the heart of the operation of the biomass-fueled organic waste shredder. From the research results, the biomass-fueled organic waste chopper machine cannot operate because of the limited energy generated by burning biomass (wood pellets) so that it cannot move the dynamo to operate the chopper.